1986
DOI: 10.1099/0022-1317-67-9-1851
|View full text |Cite
|
Sign up to set email alerts
|

Zosteriform Spread of Herpes Simplex Virus Type 2 Genital Infection in the Guinea-pig

Abstract: SUMMARYA model of herpes simplex virus type 2 (HSV-2) infection was developed in the guinea-pig that permits investigation of the role of neural spread of virus in the pathogenesis of genital skin disease. After HSV-2 inoculation of an abraded area lateral to the external genital skin, virus was first detected in the ipsilateral (to the inoculation site) peripheral nerves or genital skin on day 2 or 3 post-inoculation followed by detection in the ipsilateral dorsal root ganglia and spinal cord on day 3 or 4. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…By 12 to 14 days the clinical effects of primary infection have subsided, infectious virus cleared and latent infection established. It is probable that a similar course of events occurs in humans infected with HSV [4,7,29,36]. Therefore, since active virus replication may occur at a number of points in vivo, vaccination could interfere with establishment of latency by enhancing immune responses at these points.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…By 12 to 14 days the clinical effects of primary infection have subsided, infectious virus cleared and latent infection established. It is probable that a similar course of events occurs in humans infected with HSV [4,7,29,36]. Therefore, since active virus replication may occur at a number of points in vivo, vaccination could interfere with establishment of latency by enhancing immune responses at these points.…”
Section: Discussionmentioning
confidence: 95%
“…Studies in experimental animals indicate that a number of stages can be recognised during primary infection with HSV and the establishment of latency [4,5,17,43,46]. Although studies with mutant viruses have suggested that virus replication may not be essential for establishment of latency in vivo [45], in most natural and experimental infections with wild type viruses, the first stage is a period of local replication at the inoculation site.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the delayed and decreased dose reduced recurrent disease, but to a lesser extent than earlier and higher dosing did. Since HSV enters peripheral nerves and infects dorsal root ganglia at about 2 to 3 days after genital inoculation of guinea pigs (3,26), it is not surprising that delayed therapy was somewhat less effective in reducing recurrences than was treatment that was begun prior to ganglionic involvement. It appeared, however, that therapy that was begun even 36 h after viral inoculation decreased latent infection, because we observed significant differences in the recovery of latent virus from R837 recipients versus that from placebo recipients, and latent virus was only recovered from R837 recipients when HMBA was added to the explant culture.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous findings in the guinea pig model of vaginal HSV-2 infection as well as with studies of human sacral ganglia which indicate HSV-2 latency is widespread. Bernstein and Stanberry performed a detailed analysis of primary vaginal HSV-2 infection in the guinea pig and found that HSV-2 was detected from ipsilateral dorsal root ganglia on days 2 and 3 postinfection and from contralateral dorsal root ganglia on days 4 and 5 and that the majority (9/12) of animals shed virus on the contralateral genital skin from the initially infected ganglion (28), suggesting that HSV-2 infection can spread throughout neuronal tissues. Although data on the distribution of HSV-2 in human sacral ganglia are limited, Obara et al described PCR and in situ hybridization evidence of widespread sacral ganglion infection in three persons coinfected with HSV-1 and HSV-2, with HSV-2 detected in 21 of 23 sacral ganglia and HSV-1 in 22 of 23 ganglia (29), and concluded that both HSV-1 infection and HSV-2 infection are latent bilaterally throughout the sacral ganglia.…”
Section: Discussionmentioning
confidence: 99%